Assembly of cellulose nanocrystals and clay nanoplatelets studied by time-resolved X-ray scattering. Issue 23 (21st May 2021) - Munier, Pierre; Di, Andi; Hadi, Seyed Ehsan; Kapuscinski, Martin; Segad, Mo; Bergström, Lennart
Abstract : Co-assembly of cellulose nanocrystals (CNC) and montmorillonite (MNT) in levitating droplets was followed by time-resolved SAXS. The assembly was dominated by CNC, and MNT influenced the gelation and close packing at high volume fractions. Abstract : Time-resolved small-angle X-ray scattering (SAXS) was used to probe the assembly of cellulose nanocrystals (CNC) and montmorillonite (MNT) over a wide concentration range in aqueous levitating droplets. Analysis of the SAXS curves of the one-component and mixed dispersions shows that co-assembly of rod-like CNC and MNT nanoplatelets is dominated by the interactions between the dispersed CNC particles and that MNT promotes gelation and assembly of CNC, which occurred at lower total volume fractions in the CNC:MNT than in the CNC-only dispersions. The CNC dispersions displayed a d ∝ ϕ −1/2 scaling and a low- q power-law exponent of 2.0–2.2 for volume fractions up to 35%, which indicates that liquid crystal assembly co-exists and competes with gelation.